Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4028/www.scientific.net/ssp.280.142
|View full text |Cite
|
Sign up to set email alerts
|

Microwave and Electrical Properties of Zr-Doped SrTiO<sub>3</sub> for Dielectric Resonator Antenna Application

Abstract: Present investigation provides experimental studies on cylindrical dielectric resonator antennas (CDRAs) fabricated from SrTi1-xZrxO3ceramic with different substitution of Zr in place of Ti for (0 ≤ x ≤1). Ceramic powder were prepared using conventional solid state reaction method. X-ray Diffraction exposes physical properties Zr-doped SrTiO3which exhibit phase transition from cubic, tetragonal to orthorhombic phase. The electrical properties such as dielectric constant (εr) and dielectric loss (tan δ) were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 12 publications
(11 reference statements)
0
0
0
Order By: Relevance
“…Numerous attempts have been exerted to further improve the properties of SrTiO 3 -based ceramics. Doping is considered an effective approach for altering their properties [2]. Reproducible resistive switching behaviors have been observed in doped perovskite oxide films [3,4], such as Mo-doped SrTiO 3 [5], Mg-doped SrTiO 3 [6], Nb-doped SrTiO 3 films [7], and Ni-doped SrTiO 3 films [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous attempts have been exerted to further improve the properties of SrTiO 3 -based ceramics. Doping is considered an effective approach for altering their properties [2]. Reproducible resistive switching behaviors have been observed in doped perovskite oxide films [3,4], such as Mo-doped SrTiO 3 [5], Mg-doped SrTiO 3 [6], Nb-doped SrTiO 3 films [7], and Ni-doped SrTiO 3 films [3].…”
Section: Introductionmentioning
confidence: 99%
“…Reproducible resistive switching behaviors have been observed in doped perovskite oxide films [3,4], such as Mo-doped SrTiO 3 [5], Mg-doped SrTiO 3 [6], Nb-doped SrTiO 3 films [7], and Ni-doped SrTiO 3 films [3]. Several studies have indicated that Zr 4+ in SrTiO 3 can stabilize the charge of Ti 4+ and suppress oxygen dissociation [1,2,8]. In addition, our previous study showed that the addition of Zr can effectively improve the surface morphology of insulators [9].…”
Section: Introductionmentioning
confidence: 99%